HIV-1–neutrophil interactions trigger neutrophil activation and Toll-like receptor expression (2023)
Although neutrophils are the first-line of host defense against infection and express a wide number of pattern recognition receptors (PRRs), the function of these PRRs, including Toll-like receptors (TLRs), in HIV-1 infection remains unclear. TLRs play an important role in innate immunity, and while their involvement in viral immune pathogenesis was recently proposed, little is known about their expression and function during the neutrophil response to HIV-1 exposure. Here, we have shown that freshly isolated human neutrophils from healthy donors exhibited altered TLR expression, which may affect their function, after being challenged with HIV-1, alone or in the presence of TLR agonists. TLRs may promote neutrophil activation, pro-inflammatory cytokine secretion, and the production of reactive oxygen species. To our knowledge, this study is the first demonstration of functional TLR expression on neutrophils in response to HIV-1 treatment, suggesting a possible neutrophil/HIV-1 interaction through TLRs. Although additional studies are required to confirm the function of TLRs in neutrophils, our data clearly suggest that they play a role in the regulation of innate immunity by neutrophils, which could be engaged in HIV-1 pathogenesis or host defense. © 2015, Springer Science+Business Media New York.